Citotoxicidade de dois cimentos à base de silicato de cálcio - Estellita, Raffaella Sacchetti (2017)
The aim of the present study was to evaluate MTA White and TheraCal LC Cytotoxicity. Control group used was treated with convencional cellular medium. The Cytotocity was determined by counting viable cells using the MTT colorimetric Assay. The extract of the materials was used undiluted and an experimental contact Time for 24 hours. Data from the MTT assay was performed using SPSS version 15.0 statistical software (SPSS, INC, Chicago,IL, USA). Data were tested for Normal distribution by the Kolmogorov-Smirnov test, and group comparisons were Analysed by one-way analysis of variance (ANOVA) followed by a Bonferroni post- test. The results showed statistically significant differences between the materials Testd ( P> 0.05 ) and between the materials and the control group ( P> 0.5 ). Its is Concluded that, within the limitations of the study, ther is difference between a MTA cytotoxicity where when compared to the TheraCal LC.